Low wear braking material with high friction coefficient. (September 2022) - Shang, Xi; Yu, Kun; Zuo, Xiaochao; Yang, Huaming
Abstract: The addition of high-hardness friction-increasing fillers causes additional wear and tear, resulting in significant dust and pollutants. In this paper, the role of fluorite, a strategic resource with moderate hardness, in an environmentally friendly friction material with a low wear rate and a high friction coefficient is investigated for the first time. The effects of fluorite on the physical, mechanical, and friction properties of friction composites were explored. It is shown that weak chemisorption between fluorite and phenolic resin improves the binding ability. Meanwhile, fluorite can inhibit the degradation of phenolic resin, improve the thermal stability of friction materials, and effectively reduce the wear rate. This study provides a theoretical guidance for the development of mineral applications in friction materials.